Deficiency of WARS2, encoding mitochondrial tryptophanyl tRNA synthetase, causes severe infantile onset leukoencephalopathy. Issue 9 (26th June 2017) - Theisen, Benjamin E.; Rumyantseva, Anastasia; Cohen, Julie S.; Alcaraz, Wendy A.; Shinde, Deepali N.; Tang, Sha; Srivastava, Siddarth; Pevsner, Jonathan; Trifunovic, Aleksandra; Fatemi, Ali
Abstract : Pathogenic variants in the mitochondrial aminoacyl tRNA synthetases lead to deficiencies in mitochondrial protein synthesis and are associated with a broad range of clinical presentations usually with early onset and inherited in an autosomal recessive manner. Of the 19 mitochondrial aminoacyl tRNA synthetases, WARS2, encoding mitochondrial tryptophanyl tRNA synthetase, was as of late the only one that had not been associated with disease in humans. A case of a family with pathogenic variants in WARS2 that caused mainly intellectual disability, speech impairment, aggressiveness, and athetosis was recently reported. Here we substantially extend and consolidate the symptomatology of WARS2 by presenting a patient with severe infantile‐onset leukoencephalopathy, profound intellectual disability, spastic quadriplegia, epilepsy, microcephaly, short stature, failure to thrive, cerebral atrophy, and periventricular white matter abnormalities. He was found by whole‐exome sequencing to have compound heterozygous variants in WARS2, c.938A>T (p.K313M) and c.298_300delCTT (p.L100del). De novo synthesis of proteins inside mitochondria was reduced in the patient's fibroblasts, leading to significantly lower steady‐state levels of respiratory chain subunits compared to control and resulting in lower oxygen consumption rates.